Banking system - Kostіuk, Viktoriia; Muravskyi, Oleksii; Faychuk, Olga; Shvets, Nataliia; Rudevska, Viktoriia (Publish center NUBiP of Ukraine, 2026)
In the context of global economic processes and Ukraine's integration into the world economy, the issue of forming an effective banking system that meets the requirements and needs of the modern financial market is of great importance. Dynamic changes in the business environment and growing competition in the banking sector necessitate a review of traditional approaches to both the strategy for developing the banking system and the range of banking operations and services. In recent years, the Ukrainian banking system, like the country as a whole, has been operating under challenging conditions of financial and economic crisis, necessitating urgent and effective reforms. A reduction in production, devaluation of the national currency, inflationary pressure on the economy, and a decrease in investment activity have complicated the functioning of the banking sector of the economy. The lack of modern development strategies aimed at stabilizing the banking system's functioning and increasing its role in ensuring the sustainable development of the real sector of the economy and the social sphere negatively affects banks' ability to provide the economy with financial resources. Among the causes of negative phenomena in the financial and credit sector of the Ukrainian economy, the unsatisfactory state of bank management occupies a significant place. Under such conditions, the constant increase in requirements for the training of banking specialists with a high level of knowledge in the field of banking information technologies and financial innovations becomes of primary importance. The quality of bank management is a key factor in determining the competitiveness and financial stability of individual banks, as well as the efficiency and stability of the banking system as a whole. The study guide "Modern banking: theory and practice" is designed to form students' theoretical knowledge system about the functioning of the banking system, the principles of organizing the central bank’s work, and the essence and methodology of commercial bank operations. An important task is to equip students with practical work skills in various areas of banking, including operational activities, banking management, marketing, banking risk management, and the application of the latest banking technologies. The training manual was developed in accordance with current Ukrainian legislation and the National Bank of Ukraine's regulations, taking into account modern banking practices and standards. The manual can be helpful for students, postgraduates, and teachers of economic specialties of higher educational institutions, as well as for economists, bankers, and clients of banking institutions.
Recommended for publication by the Academic Council of the NUBiP of Ukraine (№ 5, 27.11.2025)
Keywords: banking system; банківська система; financial market; фінансовий ринок; banking transactions and services; банківські операції та послуги; Ukrainian banking system; Українська банківська система